2005
DOI: 10.1016/j.otohns.2004.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Solitary Fibrous Tumor of the Hypopharynx With Dysphagia

Abstract: S olitary fibrous tumors are rare spindle cell neoplasms that are most commonly within the thorax, especially the pleura. The first case of this tumor arose in 1931 involving the pleura, 1 and it has since been recognized to occur in a large variety of sites. In the past 15 years, solitary fibrous tumors have been recognized in many new sites in the body. Relevant to the field of otolaryngology, this includes the epiglottis, larynx, parapharyngeal space, paranasal sinus, thyroid, and nasopharynx. Once thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 4 publications
2
30
0
1
Order By: Relevance
“…Two authors have previously reported hypopharyngeal SFTs, but both originated from the pyriform sinus [2, 3]. All three cases (including the present case) of SFT of the hypopharynx occurred in men.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Two authors have previously reported hypopharyngeal SFTs, but both originated from the pyriform sinus [2, 3]. All three cases (including the present case) of SFT of the hypopharynx occurred in men.…”
Section: Discussionmentioning
confidence: 47%
“…Our patient presented with progressive shortness of breath leading him to seek treatment, and the mass could be seen encroaching on the laryngeal inlet. Mussak et al reported that their patient, although not reporting dyspnea, had a near occlusion of the airway by the hypopharyngeal mass [2]. This has also been described in cases presenting in the larynx.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations